Analysing the Challenges of Humanitarian Workers in Provision of Assistance to Internally Displaced Persons (IDPs) in Conflict Zones: Study of North Eastern Nigeria - Fatokun, Olalekan Samuel; Olise, Mondreal Chinonso (Journal of Contemporary International Relations and Diplomacy, 2024)
This study explored the challenges encountered by humanitarian workers in providing assistance to Internally Displaced Persons (IDPs) within conflict-ridden zones, with a particular focus on North Eastern Nigeria. Amidst the turmoil of armed conflict and displacement, humanitarian workers serve as vital conduits of aid, striving to alleviate the suffering of affected populations and facilitate their transition towards sustainable recovery. These roles notwithstanding, the humanitarian workers face myriad challenges that hamper their ability to provide sustained and comprehensive aid to vulnerable populations. This study assessed the impact of existing strategies and interventions employed by humanitarian workers in addressing the diverse needs of IDPs; and analysed the specific challenges they encountered while operating in conflict zones. Human security theory was employed as the theoretical framework for the study. The study also used primary and secondary data, and employed discussion and descriptive method of analysis. Findings revealed that the humanitarian workers play a critical role in providing support to IDPs in areas such as healthcare, education, and protection. Also, findings revealed that the humanitarian workers face significant risks to their safety and security while delivering aid to IDPs within conflict zones. The study recommended enhance coordination among humanitarian organizations and government agencies to streamline efforts in providing assistance to IDPs; develop targeted interventions that address the unique needs and vulnerabilities of IDPs in conflict-affected areas; address logistical challenges and security threats that hinder the delivery of aid to conflict-affected areas, among others.